Use of Ultrasound in Introducing Anatomical Pathology to Preclinical Medical Students, in Correlation with Physical Exam Curricula - Lauren Trembley; Marek Radomski (Association of American Medical Colleges, 2020)
Introduction Point-of-care ultrasound has become an important diagnostic tool in many clinical settings. Many medical schools have responded by incorporating instruction on ultrasound into the curriculum for medical students in their clinical years. The curriculum presented here will assist preclinical medical students in distinguishing between normal and pathologic sonographic anatomical findings. Methods The course consisted of four, approximately 30-minute case-based PowerPoint slide shows introducing pathologic anatomical findings on ultrasound through clinical case-based scenarios. Twelve preclinical (first- and second-year) medical students attended each weekly session. An emergency medicine resident created and presented the course content as an adjunct to an established course instructing students on how ultrasound correlates to the normal physical exam. Upon completion of the course, the instructors emailed the students an online, seven-question survey. Results Survey results showed positive feedback, with 71% of respondents answering strongly agree to the survey question that addressed the primary educational objective, which was to enable students to distinguish between normal and pathologic anatomical findings on ultrasound. Open response feedback highlighted that the course complemented the existing course well and suggested that the course be continued. Discussion A curriculum which presents pathologic anatomical findings on ultrasound can be a useful tool in the education of preclinical medical students. Such a course enabled learners to more easily distinguish between normal and pathologic exam findings and introduced them to the many clinical uses of ultrasound at an earlier stage in their training, allowing them to develop this important skillset.